2004
DOI: 10.1023/b:bebm.0000035143.55617.04
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Evidence of Invasive Activity of Vibrio Cholerae

Abstract: The development of experimental cholera in suckling rabbits is associated with typical cholerogenic syndrome: the presence of Vibrio cholerae in the blood, bile (in 60 and 70% cases, respectively), small and large intestine (in 100% cases). Simultaneously with enterocyte desquamation and increased permeability of the blood-enterocyte barrier, the vibrios are released into villous stroma and then into the microcirculatory bed. the zot toxin is involved in the mechanism of Vibrio cholerae invasion, the correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Remarkably, majority of these vibrios have tcpA and that could suggest its role in the pathogenesis. In some of the clinical cases, it was shown that the V. cholerae non-O1 and non-O139 causes invasive infection using the Zot by increasing the permeability of epithelial barrier and destabilizing the TJs junctions (Kharlanova et al, 2004 ). Vibrio parahaemolyticus has a second T3SS2 in its chromosome-II that mediates invasion into non-phagocytic cells using an effector, VopC that has a deamidase/transglutaminase activity (Park et al, 2004 ).…”
Section: Regulation Of Invasive Mechanismsmentioning
confidence: 99%
“…Remarkably, majority of these vibrios have tcpA and that could suggest its role in the pathogenesis. In some of the clinical cases, it was shown that the V. cholerae non-O1 and non-O139 causes invasive infection using the Zot by increasing the permeability of epithelial barrier and destabilizing the TJs junctions (Kharlanova et al, 2004 ). Vibrio parahaemolyticus has a second T3SS2 in its chromosome-II that mediates invasion into non-phagocytic cells using an effector, VopC that has a deamidase/transglutaminase activity (Park et al, 2004 ).…”
Section: Regulation Of Invasive Mechanismsmentioning
confidence: 99%